1960
DOI: 10.1080/00288233.1960.10426636
|View full text |Cite
|
Sign up to set email alerts
|

The peat soils of the Auckland Islands

Abstract: This paper contains a description of the peat soils on part of the Auckland Islands which lie in the South Pacific Ocean approximatelỹ WO' miles south of New Zealand. Peat forms a blanket over the surface of the Islands and is the parent material of most of the soils. In the area examined in detail the average thickness of the peat blanket was approximately 6 feet. A fossil soil horizon in the peat was dated by the radiocarbon method as 6290 ± 110 years before present. This is tentatively correhted with the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Carbon to nitrogen ratios are low in areas with sea bird breeding (Leamy & Blakemore 1960), consistent with inputs of guano N. The relatively low C:N value found in the present study is in the middle of the range found in organic soils in sea bird breeding areas on the Snares Islands (15-31:1; Flint & Fineran 1969), and on the Auckland Islands and Campbell Island (14-34:1; Leamy & Blakemore 1960). The C:N ratio from the present study compares well with constant values of 22.1-23.3 over a depth range of 30-88 cm found adjacent to sea bird burrowing on nearby Putauhinu (DH & JN unpubl.…”
Section: Issues Relating To the Peat Resultssupporting
confidence: 60%
“…Carbon to nitrogen ratios are low in areas with sea bird breeding (Leamy & Blakemore 1960), consistent with inputs of guano N. The relatively low C:N value found in the present study is in the middle of the range found in organic soils in sea bird breeding areas on the Snares Islands (15-31:1; Flint & Fineran 1969), and on the Auckland Islands and Campbell Island (14-34:1; Leamy & Blakemore 1960). The C:N ratio from the present study compares well with constant values of 22.1-23.3 over a depth range of 30-88 cm found adjacent to sea bird burrowing on nearby Putauhinu (DH & JN unpubl.…”
Section: Issues Relating To the Peat Resultssupporting
confidence: 60%
“…The publications of the 50s and 60s reported the research conducted by Taylor (1955) on the soils of Macquarie Island, by Leamy and Blakemore (1960), on Auckland Island, by Holdgate et al (1967) and Allen et al 1967), on Campbell Island (Campbell 1981), on Signy Island, and by Everett (1976) on the Antarctic Peninsula. Starting with the 1980s and continuing to the present there has been an increase in soil investigations in the ice-free coastal areas of East Antarctica and outside of conterminous Antarctica.…”
Section: History Of Soil Investigations In Antarcticamentioning
confidence: 95%
“…He suggested that the expansion of M etrosideros occurred during the warm phase of the 12th century, but more recent studies indicate that this event was thousands of years, rather than hundreds of years, old. Leamy and Blakemore (1960) reported a radiocarbon age of 6290 ± 110 yr BP (NZ 313) for peat from the lower half of a profile at the head of the first bay north-northwest of Ranui Cove, and pollen analysis of that peat provided a spectrum (Table 2) which could be equated with the older grassland-shrubland stage of the published pollen diagrams. In Jhnuary 1966, Dr P. Johns, Zoology Department, University of Canterbury, collected a sample from a peat layer 0.15 m thick lying between layers of gravel near the top of a 15 m high cliff at Musgrave Peninsula, Auckland Island.…”
Section: Previous Workmentioning
confidence: 99%